The metalloproteinase inhibitor Reck is essential for zebrafish DRG development - Prendergast, Andrew (Company of Biologists, 2012)
The neural crest is a migratory, multipotent cell lineage that contributes to myriad tissues, including sensory neurons and glia of the dorsal root ganglia (DRG). To identify genes affecting cell fate specification in neural crest, we performed a forward genetic screen for mutations causing DRG deficiencies in zebrafish. This screen yielded a mutant lacking all DRG, which we named sensory deprived (sdp). We identified a total of four alleles of sdp, all of which possess lesions in the gene coding for reversion-inducing cysteine-rich protein containing Kazal motifs (Reck). Reck is an inhibitor of metalloproteinases previously shown to regulate cell motility. We found reck function to be both necessary for DRG formation and sufficient to rescue the sdp phenotype. reck is expressed in neural crest cells and is required in a cell-autonomous fashion for appropriate sensory neuron formation. In the absence of reck function, sensory neuron precursors fail to migrate to the position of the DRG, suggesting that this molecule is crucial for proper migration and differentiation.